Arsenic Intake through Consumed Rice in Iran: Markets Role or Government Responsibility - Sepideh Nemati; Mohammad Mosaferi; Alireza Ostadrahimi; Amir Mohammadi (Health Promotion Perspectives, 2014)
Background: the present study investigated arsenic content in Iranian, imported rice on sale in Tabriz (fourth most populous city of Iran) market, and assesses daily arsenic intake from rice. Methods: A total of 33 locally available rice samples from different brands were collected and then wet and dry ashing digestion procedures were compared for decomposition of them before analyzing by graphite furnace atomic absorption spectrometry (GFAAS). Results: The mean arsenic concentration in Iranian rice was 0.065 mg/kg versus 0.082 mg/kg in imported samples. There was no significant difference between arsenic concentrations between two groups of samples (P=0.061). The average daily ingestion rate of total arsenic was 0.11 and 0.15 μg/kg body weight from consumption of 110g of Iranian and imported rice respectively. Conclusion: Based on our estimation, daily dietary intake of arsenic from Iranian and imported rice was approximately 7 and 9 μg/day for local population, respectively.All of the rice grains that were sampled from Tabriz market were low in total arsenic compared to the standard. Nonetheless regular monitoring of all rice varieties should be continued.